The vernacular press in Padang, 1865-1913 - Ahmat Adam, (Universiti Kebangsaan Malaysia, 1975)
This paper is an attempt to study the development of the vernacular press in Padang, the capital city of the residency of Sumatra West Coast. While tracing the growth of the native press in Padang, its role as an agent of change as well as the people involved in the press business itself, attention will also be focused on the various issues brought to surface by the press such as the questions of modernization of society, religious reforms and the conflicts between the traditional and progressive leaderships reflected in the polemics between the kaum tua and kaum muda groups in Sumatra West Coast.